Internet use, socioeconomic status, and smoking behaviors among Chinese men: A secondary longitudinal dataset analysis of the China Family Panel Study. - Yuan, Hao; Wu, Fanrong (Tobacco Induced Diseases, 2026)
Introduction: Despite intensified tobacco-control efforts, male smoking prevalence in China has decreased, but remains high at 45%. With the rapid development of the Internet, the influence and strength of Internet use on smoking behaviors are unclear in China. This study tests whether socioeconomic status and Internet use, respectively, are positively associated with smoking behaviors among Chinese men, and examines the moderating effects of Internet use in the correlation between socioeconomic status and smoking behaviors. Methods: This is a secondary dataset analysis using data from the China Family Panel Study (2014–2022), involving 8916 male participants aged ≥16 years. Key variables included daily cigarette consumption (outcome), socioeconomic status (household income, education level, occupation), and Internet use (access, online chatting/learning/shopping/entertainment). This study applies two-way fixedeffects negative-binomial models to assess the moderating effect of Internet use. Results: Higher SES (higher income: IRR=1.03; 95% CI: 1.02–1.04, p<0.001; education level: IRR=1.01; 95% CI: 1.01–1.02, p<0.001) is associated with increased daily cigarette consumption. Internet use is also positively related to daily cigarette consumption (IRR=1.03, 95% CI: 1.02–1.04, p<0.001). Income strengthens the association between Internet use and smoking behaviors (interaction effect: IRR=1.005; 95% CI: 1.001–1.009, p<0.01), while more years of schooling weakens this relationship (interaction effect: IRR=0.998; 95% CI: 0.996–0.999, p<0.001). Moreover, being out of the labor force can also weaken the Internet-smoking link (interaction effect: IRR=0.962; 95% CI: 0.947–0.977, p<0.001). Conclusions: Socioeconomic status and Internet use are positively related to smoking behaviors. Economic advancement can strengthen the impact of Internet use on DCC, but education level and employment status make Internet use much less important for smoking behaviors. Therefore, tobacco control interventions could incorporate online outreach approaches, with targeted initiatives developed specifically for males of high socioeconomic status with frequent online access. Policymakers are strongly encouraged to develop and implement more comprehensive, forward-looking tobacco control strategies that are specifically tailored to the online environment.